Proceedings of the Eleventh ACM SIGKDD International Conference on Knowledge Discovery in Data Mining 2005
DOI: 10.1145/1081870.1081927
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic syslog mining for network failure monitoring

Abstract: Syslog monitoring technologies have recently received vast attentions in the areas of network management and network monitoring. They are used to address a wide range of important issues including network failure symptom detection and event correlation discovery. Syslogs are intrinsically dynamic in the sense that they form a time series and that their behavior may change over time. This paper proposes a new methodology of dynamic syslog mining in order to detect failure symptoms with higher confidence and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(89 citation statements)
references
References 26 publications
(27 reference statements)
0
89
0
Order By: Relevance
“…Several studies about system monitoring have demonstrated the feasibility of such an approach [28], [29]. Although those works present important results about system monitoring in HPC, they do not try to make the connection with different failure regimes and dynamic resilience runtime in order to minimize wasted time.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies about system monitoring have demonstrated the feasibility of such an approach [28], [29]. Although those works present important results about system monitoring in HPC, they do not try to make the connection with different failure regimes and dynamic resilience runtime in order to minimize wasted time.…”
Section: Related Workmentioning
confidence: 99%
“…Different analysis tasks pay attention to different application aspects, such as system failure tracing [19,10], event correlation discovery [20,18,16], and event based trend analysis [5,6,7]. In practice, these methods are often conducted when the analysts already have some prior knowledge about the data.…”
Section: Related Workmentioning
confidence: 99%
“…property values description #types 20-100 step 20 The number of event types. #events 60k-140k step 20k The number of event occurrences.…”
Section: Efficiency Evaluationmentioning
confidence: 99%
“…As a result such datasets are rarely available in operational networks and were not available when we first analyzed the CENIC network. Thus, in many cases, including our own previous work, network analysis is conducted using syslog data [4,10,14,15,21]. Worryingly, it remains unknown what sacrifices a syslogbased approach makes in terms of accuracy when compared to the ground truth revealed via routing protocol messages.…”
Section: Introductionmentioning
confidence: 99%